2021
DOI: 10.1021/acscatal.0c05104
|View full text |Cite
|
Sign up to set email alerts
|

Core–Shell Double Doping of Zn and Ca on β-Ga2O3 Photocatalysts for Remarkable Water Splitting

Abstract: Photocatalytic water splitting reaction attracts considerable attention owing to their potential application to generate H 2 gas from H 2 O by using solar energy. However, further activity enhancement is indispensable for industrial use. Various approaches have been adopted to improve its activity; however, as these defects and impurities are the main obstacles that reduce quantum efficiency (QE), the fabrication of fine crystals with low defects and impurities has been essential for activity improvement. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 50 publications
1
32
0
Order By: Relevance
“…These data reflect the dynamics of the intraband transitions of free and/or shallowly trapped electrons and photoexcited holes, respectively. 23,24 The addition of 1 mol% Zr evidently increased the lifetime of shallowly trapped electrons, in agreement with earlier work by Hojamberdiev et al, 25 but had no appreciable effect on the dynamics of trapped holes. Doping with lower valence cations may suppress the formation of reduced Ta species acting as recombination centers.…”
Section: Resultssupporting
confidence: 90%
“…These data reflect the dynamics of the intraband transitions of free and/or shallowly trapped electrons and photoexcited holes, respectively. 23,24 The addition of 1 mol% Zr evidently increased the lifetime of shallowly trapped electrons, in agreement with earlier work by Hojamberdiev et al, 25 but had no appreciable effect on the dynamics of trapped holes. Doping with lower valence cations may suppress the formation of reduced Ta species acting as recombination centers.…”
Section: Resultssupporting
confidence: 90%
“…However, the decay of deeply trapped electrons was drastically accelerated by the formation of oxygen vacancies, even after a few picoseconds. It has been reported that defects such as oxygen vacancies introduced in TiO 2 , , SrTiO 3 , , and Ga 2 O 3 , could increase the lifetime of photocarriers since these defects capture photoelectrons and reduce the probability of their recombination with holes, as shown in Scheme a. These trapped electrons need to travel long distances between defects by repeated hopping and tunneling.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The results of the study of defect species described above were further supported by the transient absorption (TA) kinetic profiles of charge carriers probed at 2000 cm –1 (5000 nm) on a microsecond time scale (Figure a), reflecting the intraband transition of free and/or shallowly trapped electrons in/near the conduction band of the various Ta 3 N 5 . Undoped Ta 3 N 5 exhibited the lowest TA intensity along with fast decay due to the rapid trapping of electrons at deep states, most likely arising from Ta 3+ (Figure f), a well-known recombination center in Ta 3 N 5 . ,, Ta 3 N 5 :Zr, which had the fewest defect species, produced significantly higher TA intensity at 2000 cm –1 (5000 nm) with slower decay than Ta 3 N 5 :Mg, which contained more V N . However, defining the functionality of each individual type of V N (V N •• and V N ••• /V N • ) remains difficult due to the complex transformation from each other upon photoexcitation.…”
mentioning
confidence: 63%